Women's Leadership in Quality Management Development and Gender Equality within the Context of Nahdlatul Ulama Universities in Indonesia - Rohmatun Lukluk Isnaini (Universitas Islam Negeri Sunan Kalijaga Yogyakarta, 2021)
To date, the women's leadership in Indonesian Universities (Higher Education Institutions) is still far from equal. However, there is a new history in the placement of women's leadership in the development of quality management at the Nahdlatul Ulama Universities (PTNU). Using an exploratory research method, this study aims to reveal the experiences of women leaders in the development of quality management and gender equality at PTNU. Data collection was carried out by in-depth interviews with 8 female leaders who held structural positions as Vice Rector, Chair of LPM, Dean, and Head of Undergraduate Program. The results of this study indicate the following 3 important points: (1) The experience of women's leadership at PTNU shows that women's leadership has gained important positions in structural positions because of (a) considerations of competence and performance, (b) the cooperative and patient attitude of female leaders which makes them to earn appreciation from all academicians, and (c) the track record of female leaders who have increasingly improved their leadership achievements in the development of quality management; (2) Supporting factors in women's leadership, influenced by support from colleagues and adequate facilities; and (3) Inhibiting factors for women's leadership in developing quality management are difficulties in dealing with different commitments from each employee, still limited competent human resources, and it is still difficult to cultivate quality. Meanwhile, the obstacles to the efforts in gender equality are the limited female human resources, the lack of willingness of women to become leaders, and overlapping jobs. Recommendations from the results of this study can be used as a basis for university leaders, especially PTNU in making policies in the domain of quality management and gender equality.